Penguatan Kemandirian Ekonomi Melalui “Program Bara Agro Sirkular” pada Perkebunan Kabupaten Muara Enim untuk Mendukung Kesehatan Lingkungan dan Kesejahteraan Masyarakat - Nurbaiti Nurbaiti; Sarmidi Sarmidi; Putra Putra; M. Syaiful (Jurnal Medika: Medika, 2026)
The Bara Agro Circular Program is an initiative of PT Bukit Asam Tbk – Tanjung Enim Mining Site (PTBA-TEMS) designed to empower communities surrounding the company’s operational areas through a circular economy approach, specifically within the plantation subsector. This program aims to enhance community welfare by integrating sustainable and efficient plantation practices. This study analyzes the social, economic, and environmental impacts of the implementation of the Bara Agro Circular Program with a focus on plantation activities. Data collection methods included surveys of plantation farmers, observation of agricultural practices, and in-depth interviews with key stakeholders. The collected data comprised information on productivity improvements, technology adoption, changes in income, and environmental impacts resulting from the implemented plantation practices. The findings indicate a significant increase in farmers’ knowledge of modern and sustainable plantation techniques, improved crop yields, and rising income levels. The utilization of plantation waste as compost also contributed to improving soil quality and reducing the use of chemical fertilizers. Furthermore, the program encouraged crop diversification, strengthened community economic resilience, and created new employment opportunities. Therefore, the Bara Agro Circular Program can serve as an effective model for sustainable plantation development and community empowerment in mining regions.